Organization of career support and development by means of building an individual educational trajectory - M.G., Sergeeva (2019)
The current stage of socio-economic development of Russia is characterized by intensive changes in the field of interaction between the labor sphere and the education system. In terms of the organization of career support and development as a structural unit of the pedagogical process aimed at the development of the function of self-realization of the individual, we consider the situation of self-realization as a complex multilateral phenomenon, causing the result of the assimilation of material and personal development. A prerequisite for the development of educational trajectories is the developed and implemented in practice monitoring system, which is based on the following principles: purposefulness, continuity, integrity and diversity, consistency of actions of its subjects, targeting and publicity of the extracted information. A necessary condition for the development of educational trajectories is continuity, which provides: the unity of goals and objectives of the educational process; the content and methods of work of the teacher and students at all stages of their development; common understanding of the development laws, which reveal the relationship of learning, education and personal development. Analysis of the forms of joint activities of different educational institutions found that multi-level integrated training of specialists is carried out on the basis of the interaction of different types of professional educational institutions that retain legal independence, and meaningful one – on the basis of successive curricula and optimization of the content of academic disciplines. There are a number of problems that are being slowly solved: training of professional personnel lags behind the pace of structural adjustment of high-tech industries, there is a “washing out” of high-tech expensive specialties, the demand of national production is significantly ahead of the supply of educational institutions in terms of volumes and structure of personnel training, etc.